Actin nucleoskeleton in embryonic development and cellular differentiation. (June 2022) - Gunasekaran, Sivagami; Miyagawa, Yasuki; Miyamoto, Kei
Abstract: Dynamic assembly and disassembly of actin proteins play a key role in the cytoskeleton, but the cellular functions of actin are not only restricted to the cytoplasmic compartment. Recent studies have shown that actin spatiotemporally changes its polymerized state in the nucleus as well and such dynamic nature of actin is relevant to key nuclear events including gene expression, DNA damage response and chromatin organization. In this review, we highlight emerging roles of actin in the nuclear compartment especially in the context of embryonic development and cellular differentiation. We first explain how the actin nucleoskeleton can be formed and function in cells. Notably, nuclear actin dynamics are greatly altered when cell fates change, such as after fertilization and T cell differentiation. We discuss how the dynamic actin nucleoskeleton contributes to accomplishing developmental programs. Graphical abstract: Image 1 Highlights: Dynamic assembly and disassembly of nuclear actin form the nucleoskeleton. The actin nucleoskeleton is involved in numerous nuclear events. Spatiotemporal control of nuclear actin assembly is key to embryonic development. The actin nucleoskeleton is responsible for cell fate changes in multiple cell types.